COMPREHENSIVE ANALYSIS OF HEALTHCARE FINANCING MODELS AND EXPLORING UNIVERSAL HEALTH COVERAGE, HEALTH INSURANCE, AND PAYMENT REFORMS - 1Abdulrahman Hussain Alsharif, 2Musleh Hussain Musleh Aglah, 3Fahad Mana Aboraseen, 4Fadhel Ali Al-Abbas, 5Hashem Mohammed Yahya Alshareef, 6Khaled Hassan M Alshareef (Chelonian Research Foundation, 2022)
This comprehensive analysis delves into healthcare financing models, exploring universal health coverage (UHC), health insurance, and payment reforms.It analyzes the viability, challenges, and impacts of different money-related rebels in accomplishing value in healthcare. By analyzing distinctive models from around the world, this investigation aims to identify the qualities and shortcomings of each approach and give suggestions for advancement, progressing healthcare frameworks to attain widespread scope, and moving forward open healthcare outcomes. Keywords: healthcare financing, universal health coverage, health insurance, payment reforms, equitable access, population health